Sensitivity Analysis of Catchment Characteristics in Urban Stormwater Management Modeling - Basnayaka, Amila; Sarukkalige, Priyantha (Research Publishing Services, 2012)
Numerical stormwater management modeling helps to understand the urban hydrological catchment behavior. Urban hydrological modeling is a complex process, when considering all the urban hydrological catchment characteristics. Selecting and/or prioritizing catchment characteristics according to their sensitivity on modeling results helps to generate simplified and accurate catchment models. Sensitivities of selected catchment characteristics depend on land use change have been analyzed by hydrological modeling of an urban catchment. Changes to surface roughness coefficients increased the modeled post development peak flow up to 10.3% and 15.5% in 1 year and 100 year ARI events. Changing of infiltration parameters caused to 8.8% and 0.3% changes in peak flows under two scenarios. These results show that the sensitivity of parameters associated with the portion of impervious land use is more significant than the characteristics associated with the pervious land use portion. Results have suggested that the overall land use change is more sensitive to the modeling results of minor rainfall events than the results of major rainfall events. Results will help to decide most sensitive catchment characteristics and applicable range of their values, when modeling similar urban catchments.